“Google Books” and mass digitization: The contribution of the Complutense University of Madrid - Magán Wals, José Antonio; Tardón González, Eugenio (Revista General de Información y Documentación, 2014)
Study of mass digitization project that has enabled Google Books scan more than 20 million books worldwide (80% from participating libraries and the rest from more than 50,000 publishers participating in the program). The Library of the Complutense University of Madrid joined in 2006 and 120.574 books were scanned. These are now available in Google, UCM's catalogue and databases, Europeana and Hathi Trust. This has improved the dissemination and preservation of this bibliographic heritage.
Keywords: Google Books; mass digitization; Hathi Trus; Europeana; copyright; fair use; digital preservation; digital libraries